The Financial Stress Index: Identification of systemic risk conditions - Mikhail V. Oet; John M. Dooley; Stephen J. Ong (Risks, 2015)
This paper develops a financial stress measure for the United States, the Cleveland Financial Stress Index (CFSI). The index is based on publicly available data describing a six-market partition of the financial system comprising credit, funding, real estate, securitization, foreign exchange, and equity markets. This paper improves upon existing stress measures by objectively selecting between several index weighting methodologies across a variety of monitoring frequencies through comparison against a volatility-based benchmark series. The resulting measure facilitates the decomposition of stress to identify disruptions in specific markets and provides insight into historical stress regimes.
Keywords: 330; financial stress; systemic conditions; crisis identification; financial system stability; systemic risk; early warning system